A Poem by Vladimir Mikhail Kheraskov: Historical Sources - Anastasia V. Semenova (Studia Litterarum, 2019)
The article examines historical sources of the poem Vladimir by Mikhail Kheraskov (1785, 3d ed. 1797). It focuses on the following aspects: 1) the image of philosopher Cyrus, a key character in the poem, the main mentor of Prince Vladimir; 2) description of the images of the Last Judgment, heaven and hell on the “Charter” (veil) presented by Cyrus to Vladimir; 3) Vladimir’s son Vsevolod’s duel with Pecheneg. The last episode is an additional storyline that appeared only in the third edition. The sources of the poem include The Tale of Bygone Years, The Russian Chronicle according to the Nikon Lis (1767), The Kiev Synopsis (1674), The Core of Russian History (1770), and historical works of V. Tatishchev, M. Lomonosov, M. Shcherbatov, and Catherine II. The article draws parallels between the poem and these sources, including textual parallels. In conclusion, it is argued that in “Vladimir,” as earlier in “Rossiyada”, the poet whenever possible relates his narrative to historical evidence, constantly borrows from different sources. This concerns important ideological aspects of the poem (for example, the image of the main preacher, which also has Masonic connotations) as well as adventurous battlefield episodes (i.e. Vsevolod’s adventures), introduced, according to the author’s design, primarily to entertain young readers.